Caregiver‐reported dementia as a predictor of oral health among patients receiving home‐visit dental treatment: A retrospective cohort study - Satoshi Yamaguchi (Clinical and Experimental Dental Research, 2021)
Abstract Objective To assess caregiver‐reported dementia as a risk factor for retained roots, an indicator of poor oral hygiene, among patients receiving home‐visit dental treatment in Japan. Methods The medical records of 231 dentate patients who received home‐visit dental treatment (covered by public medical insurance) for more than 2 years were retrospectively analyzed. The number of teeth and retained roots at the initial and final examinations were obtained from the dental charts, and the “change in the number of retained roots from initial to final examination” was determined. The presence or absence of caregiver‐reported dementia, diabetes, and osteoporosis, as well as the level of long‐term care needed, were used as indicators of general health condition at the initial interview. Multiple regression analyses were conducted in five models that tested the association of independent variables (age, gender, observation period, general health, presence or absence of caregiver‐reported dementia at the initial interview) with changes in the number of retained roots. Results In all models, the presence of caregiver‐reported dementia at the initial interview was significantly associated with the change in the number of retained roots (p < .05). The adjusted coefficient of determination (R2) of model 5, which included all the predetermined independent factors, was .168. Conclusions Caregiver‐reported dementia may be a risk factor for an increase in the number of retained roots among patients who receive home‐visit dental treatment and may serve as an indicator of the need for regular and proactive oral hygiene management.